Therapeutic Effect of High-Definition Transcranial Direct Current Stimulation Combined with Suspension Exercise Training on Lower Limb Motor Function of Stroke Patients - ZHANG Haiquan; HU Chuan; HUANG Lei; LU Wei; WANG Xin (康复学报)
ObjectiveTo observe the effect of high-definition transcranial direct current stimulation combined with suspension exercise training on lower limb motor function of stroke patients.MethodsA total of 120 stroke patients treated in the department of rehabilitation medicine of the Shandong Provincial Third Hospital, Shandong University from January 2022 to February 2023 were randomly divided into control group, HD-tDCS group, suspension group and combined treatment group, with 30 cases in each group. During the course of the treatment, 4 cases dropped out because the patients were discharged from hospital and could not continue to receive treatment, including 3 cases in the control group and 1 case in the HD-tDCS group, and finally 27 cases were included in the control group, 29 cases in the HD-tDCS group, 30 cases in the suspension group and 30 cases in the combined treatment group, respectively. The control group received conventional rehabilitation treatments such as exercise therapy and neuromuscular electrical stimulation, 25 minutes a day, once a day, 5 days a week for 8 weeks. In addition to the treatment received by the control group, the HD-tDCS group received HD-tDCS treatment, in which the primary stimulation electrodes were placed at the primary motor cortex of the hemiplegic side of the brain in the M1 area (C3/C4), and the four acceptor electrodes were placed at C1/C2, C5/C6, FC3/FC4 and CP3/CP4 area about 3.5 cm around the M1 area, respectively, with a constant current intensity of 2 mA, and a current rise and fall of 30 s, 20 minutes a time, once a day, 5 days a week for 8 weeks. The suspension group received suspension exercise training based on the treatment in the control group, such as separated and combined exercise of the lower limbs on the hemiplegic side, dynamic closed-chain stabilization exercise, pelvic swing and relaxation exercise, 25 minutes a time, once a day, five days a week for eight weeks. The combined treatment group received HD-tDCS combined with suspension exercise training based on the treatment in the control group. Before treatment and after 4 and 8 weeks of treatment, the Fugl-Meyer assessment lower extremity (FMA-LE) was used to assess lower limb motor function. Berg balance scale (BBS) was used to assess balance function, functional ambulation category (FAC) scale was used to assess functional walking ability. A video gait system was used to assess gait spatial-temporal parameters (stride frequency, stride speed, stride length, and walking cycle).ResultsCompared with that before treatment, FMA-LE, BBS, FAC scores and gait spatial-temporal parameters (stride frequency, stride speed, stride length, and walking cycle) of the four groups after 4 and 8 weeks of treatment improved, and the differences were statistically significant (P<0.05). Compared with the control group, the HD-tDCS group and the suspension group at 4 and 8 weeks of treatment, FMA-LE, BBS scores of the combined treatment group were significantly higher, and FAC level and gait spatial-temporal parameters of the combined treatment group after 8 weeks of treatment improved, and the differences were statistically significant (P<0.05).ConclusionHD-tDCS combined with suspension exercise training can effectively improve lower limb motor function, balance ability and walking ability of stroke patients, which is recommended for clinical application.